IMPROVING ADVISORY SERVICES IN UZBEKISTAN IN FRAMEWORK OF AFACIRATEC PROJECT (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
Improving advisory services in Uzbekistan is a vital part of the country's development agenda, as reflected in the Agri-Food Sector Development Strategy (2020-2030). The strategy recognizes the importance of improving public sector services, opening up new markets for farmers and agribusinesses and introducing new technologies to the sector. In this endeavor, the AKIS play a decisive role, contributing directly to the achievement of many of goals.The system of knowledge and innovation in agriculture AKIS in Uzbekistan was developed by the Ministry of Agriculture of the Republic of Uzbekistan and approved by Presidential decree dated of February 3, 2021 No. UP-6159 "On further improvement of the system of knowledge and innovation, and provision of modern services in agriculture."